THE INFLUENCE OF A COMBINATION OF WALKING THERAPY AND HYDROTHERAPY TO DECREASE BLOOD GLUCOSE LEVELS IN PATIENTS WITH DIABETES MELLITUS TYPE II - Istiroha; Pratiko, Mono; Rahmawati, Rita; Fitri, Noor (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Diabetes mellitus (DM) has become a health problem in the world, and if not treated, many of the body's systems can be damaged, especially the nerves and blood vessels. This research aims to explain the influence of walking and drinking water hydrotherapy to decrease random blood sugar levels in patients with type 2 diabetes. Method. This research designed in this study was Quasi-Experimental, with the Control Group Pre-Post Test Design. The sampling method used purposive sampling. The sample of this research were 32 respondents in Sumbergede Village. The independent variable was walking therapy and drinking water hydrotherapy, while the dependent variable was random blood sugar levels in patients with type 2 diabetes mellitus. The instruments used walking SOP, hydrotherapy SOP and glucose meter. The data analysis technique used Wilcoxon Sign Rank Test. Result and Analysis. This study random blood sugar level in the treatment and control groups before intervention was hyperglycemia category and after intervention in the treatment group was mostly euglycemia while in the control group the majority hyperglycemia. The results of the Wilcoxon Sign Rank Test were ρ = 0.001 (ρ <0.05), meaning that there is a significant influence of a combination of walking therapy and hydrotherapy against random blood sugar reduction in patients with type 2 diabetes. The results of the Mann Whitney statistical test showed that the value of ρ = 0.001 (ρ <0.05), so that there was a significant difference in decreasing random blood sugar levels between the treatment group and the control group. Discussion. Walking therapy can increase blood glucose usage in active muscles. While drinking water hydrotherapy causes the breakdown of blood glucose, the combination of walking therapy and drinking water hydrotherapy can cause random blood sugar level to decrease. This study was expected to make one of the anti-diabetes medication companion therapies in reducing random blood sugar level in patients with type 2 DM.